Seleção de variedades tradicionais de feijão-caupi com competitividade com plantas daninhas - Medeiros, Isis Fernanda Silva (Universidade Federal Rural do Semi-Árido, 2018)
Cowpea is cultivated in practically all the municipalities of Rio Grande do Norte, especially by small producers. Much of the cowpea production in the state comes from the cultivation of landraces. In the region, weed control is usually done by hoeing weeds, which are expensive, time-consuming and laborious. However, if it is not carried out, the productivity of the crop may be seriously affected. A solution to minimize weed control costs is the use of landraces with competitive weed ability and, due to the genetic variability of the landraces used by the State producers, the objectives of this work were to identify cowpea landraces, grown in Rio Grande do Norte, that show competitiveness with weeds, as well as to identify the characteristics that give them competitive ability. For that, three experiments were carried out in the UFERSA experimental farm, in the randomized block design with five replicates. In the first experiment, 48 cowpea landraces in moderate competition with weeds were evaluated for yield of dry grains. In the second experiment, twelve landraces with the highest yields in the first experiment were evaluated, even in moderate competition with weeds; and in the third experiment, the three best and the three worst landraces were evaluated for yield in the first experiment, now under two weed controls (one weeding and two weedings). In this experiment, the weeds control corresponded to the plot, and the landraces, to the subplots. The cowpea landraces differed with respect to weed competitiveness, so that the Umarizal and Itaú landraces showed greater competitiveness with weeds than the others, these were also the landraces that presented the highest yields of green and dry grains. Weed controls did not interfere with the yield of green and dry grains. The most suitable characteristic for indirect selection of the yield of green pods, green grains and dry grains is the number of plant-1 pods. A greater number of leaves of the cowpea plants can confer greater competitive ability with weeds. The São Miguel landrace presented lower yields of green and dry grains, probably because it was not adapted to the region
Keywords: Vigna unguiculata; Variedades crioulas; Competição; Controle cultural; Vigna unguiculata; Creole wines; Competition; Weeds control; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA